Association between mid-wall late gadolinium enhancement and sudden cardiac death in patients with dilated cardiomyopathy and mild and moderate left ventricular systolic dysfunction - Halliday,BP; Gulati,A; Ali,A; Guha,K; Newsome,S; Arzanauskaite,M; Vassiliou,VS; Lota,A; izgi,C; Tayal,U; Khalique,Z; stirrat,C; et al. (Circulation, 2017)
Background—Current guidelines only recommend the use of an implantable cardioverter defibrillator (ICD) in patients with dilated cardiomyopathy (DCM) for the primary prevention of sudden cardiac death (SCD) in those with a left ventricular ejection fraction (LVEF)<35%. However, registries of out-of-hospital cardiac arrests demonstrate that 70-80% of such patients have a LVEF>35%. Patients with a LVEF>35% also have low competing risks of death from non-sudden causes. Therefore, those at high-risk of SCD may gain longevity from successful ICD therapy. We investigated whether late gadolinium enhancement cardiovascular magnetic resonance (LGE-CMR) identified patients with DCM without severe LV systolic dysfunction at high-risk of SCD.Methods—We prospectively investigated the association between mid-wall late gadolinium enhancement (LGE) and the pre-specified primary composite outcome of SCD or aborted SCD amongst consecutive referrals with DCM and a LVEF≥40% to our center between January 2000 and December 2011, who did not have a pre-existing indication for ICD implantation.Results—Of 399 patients (145 women, median age 50 years, median LVEF 50%, 25.3% with LGE) followed for a median of 4.6 years, 18 of 101 (17.8%) patients with LGE reached the pre-specified end-point, compared to 7 of 298 (2.3%) without (HR 9.2; 95% CI 3.9-21.8; p<0.0001). Nine patients (8.9%) with LGE compared to 6 (2.0%) without (HR 4.9; 95% CI 1.8-13.5; p=0.002) died suddenly, whilst 10 patients (9.9%) with LGE compared to 1 patient (0.3%) without (HR 34.8; 95% CI 4.6-266.6; p<0.001) had aborted SCD. Following adjustment, LGE predicted the composite end-point (HR 9.3; 95% CI 3.9-22.3; p<0.0001), SCD (HR 4.8; 95% CI 1.7-13.8; p=0.003) and aborted SCD (HR 35.9; 95% CI 4.8-271.4; p<0.001). Estimated hazard ratios for the primary end-point for patients with a LGE extent of 0-2.5%, 2.5-5% and >5% compared to those without LGE were 10.6 (95%CI 3.9-29.4), 4.9 (9